Identifikasi Potensi Air Tanah di Kawasan Kota Terpadu Mandiri (KTM) Kecamatan Silaut Kabupaten Pesisir Selatan dengan Metode Geolistrik Tahanan Jenis - Andany, Desti Wury; Afdal, Afdal; Pohan, Ahmad Fauzi (Universitas Andalas, 2021)
Research to determine ground water potential in the Kota Terpadu Mandiri (KTM), Silaut Region, Pesisir Selatan Regency, has been conducted. This study applied the Schlumberger 2D configuration of the geoelectrical method. Data collection was carried out at five sounding points with a track span of 200 m, the shortest electrode distance was 1.5 m (current electrode) and 0.5 m (potential electrode) by the amount of data 27. Data processing was performed using IPI2WIN lite version. The result show that the aquifer was found at all sounding points in the unconfined aquifer with depth of 3.5 – 9.0 m and a confined aquifer with a depth of 39.5 – 47.6 m. Drilling can be carried out on TS-1, TS-3, TS-44 and TS-5 which are confined aquifers with a depth of up to 47.6 m in a layer of clayey sand.